Digital Literacy of Students at PTKIN in Aceh - Putri, Nina Eka (Al-Hijr: Journal of Adulearn World, 2023)
From 2019 to 2023, digital use is increasingly being applied in carrying out activities of daily life, especially in the learning process in the field of education. Therefore, this study examines the extent to which students' abilities in digital use. Apart from being a symbol of the progress of a society, the ability to use digital can also prevent its users from spreading or preventing the absorption of hoax information. Therefore, this study aims to look at students' digital literacy skills in PTKIN in Aceh. This study used a qualitative descriptive method with data collection using interview techniques and analyzed using qualitative data analysis techniques. Based on the results of the study, it was found that the level of digital literacy skills possessed by students tended to be quite good, namely as much as 82%. With details in terms of internet searching aspects of 89%, in terms of hypertext navigation aspects of 72%. Then, from the aspect of content evaluation, it is 88% and from the aspect of knowledge assimilation, it is 78%.